Journal N-Pact Factors From 2011 to 2019: Evaluating the Quality of Social/Personality Journals With Respect to Sample Size and Statistical Power. Issue 4 (October 2022) - Fraley, R. Chris; Chong, Jia Y.; Baacke, Kyle A.; Greco, Anthony J.; Guan, Hanxiong; Vazire, Simine
Scholars and institutions commonly use impact factors to evaluate the quality of empirical research. However, a number of findings published in journals with high impact factors have failed to replicate, suggesting that impact alone may not be an accurate indicator of quality. Fraley and Vazire proposed an alternative index, the N-pact factor, which indexes the median sample size of published studies, providing a narrow but relevant indicator of research quality. In the present research, we expand on the original report by examining the N-pact factor of social/personality-psychology journals between 2011 and 2019, incorporating additional journals and accounting for study design (i.e., between persons, repeated measures, and mixed). There was substantial variation in the sample sizes used in studies published in different journals. Journals that emphasized personality processes and individual differences had larger N-pact factors than journals that emphasized social-psychological processes. Moreover, N-pact factors were largely independent of traditional markers of impact. Although the majority of journals in 2011 published studies that were not well powered to detect an effect of ρ = .20, this situation had improved considerably by 2019. In 2019, eight of the nine journals we sampled published studies that were, on average, powered at 80% or higher to detect such an effect. After decades of unheeded warnings from methodologists about the dangers of small-sample designs, the field of social/personality psychology has begun to use larger samples. We hope the N-pact factor will be supplemented by other indices that can be used as alternatives to improve further the evaluation of research.